Monitoring improvements in the nutritional quality of new packaged foods launched between 2016 and 2020 - Tassy, Marie; Rytz, Andréas; Drewnowski, Adam; Lecat, Alec; Jacquier, Emma F.; Charles, Véronique Rheiner (Frontiers in Nutrition, 2022)
Food and beverage companies reformulate packaged foods and to better align their products with public health policies and evolving consumer needs. The nutritional quality of packaged foods can be tracked using nutrient profiling methods. The present study compared the nutritional quality of packaged foods launched globally between 2016-18 and those launched in 2018-20, as reported in the Mintel Global New Products Database. Nutrient profiling analyses showed that the nutrient composition of product categories shifted for almost 40% of newly launched products between 2016-18 and 2018-20. For example, pizzas that had been assigned to one nutritionally homogenous category in 2016-18 separated in two nutritionally distinct subgroups in 2018-20. The new products that were reduced in protein, saturated fat, and sodium were now nutritionally distinct from the traditional pizza offer. By 2018-20 “best of category” products were significantly lower in sugar and sodium than before; however, no clear trend was observed for saturated fats, proteins, or fibers. The relative speed of product reformulation was category specific. This analysis of the Mintel Global New Products Database suggests that the WHO nutritional recommendations focusing on sugar and sodium reduction did have a positive impact on the composition of new packaged foods, whether through reformulation of existing products, launches of line extensions or new product development.